Effect of short-term fat adaptation on high-intensity training - Stepto, N. K.; Carey, A. L.; Staudacher, H. M.; Cummings, N. K.; Burke, L. M.; Hawley, J. A. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE: To determine the effect of short-term (3-d) fat adaptation on high-intensity exercise training in seven competitive endurance athletes (maximal O2 uptake 5.0 +/- 0.5 Lcenter dotminminus sign1, mean +/-SD). METHODS: Subjects consumed a standardized diet on d-0 then, in a randomized cross-over design, either 3-d of high-CHO (11 gcenter dotkgminus sign1dminus sign1 CHO, 1 gcenter dotkgminus sign1center dotdminus sign1 fat; HICHO) or an isoenergetic high-fat (2.6 g CHOcenter dotkgminus sign1center dotdminus sign1, 4.6 g FATcenter dotkgminus sign1center dotdminus sign1; HIFAT) diet separated by an 18-d wash out. On the 1st (d-1) and 4th (d-4) day of each treatment, subjects completed a standardized laboratory training session consisting of a 20-min warm-up at 65% of VO2peak (232 +/- 23W) immediately followed by 8 x 5 min work bouts at 86 +/- 2% of VO2peak (323 +/- 32 W) with 60-s recovery. RESULTS: Respiratory exchange ratio (mean for bouts 1, 4, and 8) was similar on d-1 for HIFAT and HICHO (0.91 +/- 0.04 vs 0.92 +/- 0.03) and on d-4 after HICHO (0.92 +/- 0.03) but fell to 0.85 +/- 0.03 (P < 0.05) on d-4 after HIFAT. Accordingly, the rate of fat oxidation increased from 31 +/- 13 on d-1 to 61 +/- 25 &mgr;molcenter dotkgminus sign1center dotminminus sign1 on d-4 after HIFAT (P < 0.05). Blood lactate concentration was similar on d-1 and d-4 of HICHO and on d-1 of HIFAT (3.5 +/- 0.9 and 3.2 +/- 1.0 vs 3.7 +/- 1.2 mM) but declined to 2.4 +/- 0.5 mM on d-4 after HIFAT (P < 0.05). Ratings of perception of effort (legs) were similar on d-1 for HIFAT and HICHO (14.8 +/- 1.5 vs 14.1 +/- 1.4) and on d-4 after HICHO (13.8 +/- 1.8) but increased to 16.0 +/- 1.3 on d-4 after HIFAT (P < 0.05). CONCLUSIONS: 1) competitive endurance athletes can perform intense interval training during 3-d exposure to a high-fat diet, 2) such exercise elicited high rates of fat oxidation, but 3) compared with a high-carbohydrate diet, training sessions were associated with increased ratings of perceived exertion.